Can the Manchester Triage Scale Better Predict Mortality and Outcomes When Combined with Different Frailty Tests in Geriatric Population? - Ozan Can Barlas; Kurtuluş Açıksarı; Görkem Alper Solakoğlu (Global Emergency and Critical Care)
Objective: In our study, we aimed to determine the effect of identifying patients at high risk of frailty by questioning their frailty status during triage in patients aged 65 years and older on the prediction of outcomes. Materials and Methods: Patients were classified as frail or non-frail according to their scores on frailty tests. According to the Manchester triage system, T2-T3 patients were classified as high priority and T4-T5 patients as low priority. According to the length of stay in the emergency department, patients were divided into two groups as under and over 4 h. The endpoints of the patients were hospitalization, treatments, and mortality. Patients grouped according to triage priorities and frailty risks with the program of research to integrate services for the maintenance of autonomy (PRISMA-7), identifying the seniors at risk, and FRESH tests were statistically analyzed according to separate outcomes, and the relationship between them was investigated. Results: The study was conducted with 331 elderly patients aged between 65 and 99 years with a median age of 75 years. The PRISMA-7 test predicts admission, mortality, emergency department length of stay (EDLOS) in low priority patients (p<0.05), treatment and mortality are mostly affected by triage scores, but admission and EDLOS can be predicted by frailty tools. Conclusion: The integration of frailty questioning into triage systems will prevent elderly patients presenting with atypical findings and non-specific complaints from being incorrectly classified as low triage priority.